Usability Testing on E-Commerce Shopee Based on Mobile Application with Cognitive Walkthrough Method to Increase Entrepreneurial - Attamimi, Alfarizi Alif; Tileng, Kartika Gianina (Jurnal Entrepreneur dan Entrepreneurship, 2021)
As we know, currently the use of mobile e-commerce is becoming a trend as an opening for entrepreneurs. As a supporter of creative entrepreneurship, it is necessary to develop a user interface and user experience. To create a quality mobile application, one of the steps that can be taken is to carry out a usability testing. This study aims to measure and provide recommendation for improvements in e-commerce based on the Shopee mobile application based on the results of the usability evaluation which is reviewed by Shopee users, effectiveness, efficiency and satisfaction. After conducting usability testing on e-commerce based on Shopee’s mobile apps with the cognitive walkthrough method and the System Usability Scale (SUS), the results of the research on aspects of effectiveness are 93%, the level of speed efficiency every second is 0,08 and 72% satisfaction. To increase the usability level of e-commerce based apps, this study designed a recommendation on the Shopee e-commerce application that changes the layout of the pages and menus, and the others is simplifies the display.